Effect of Spirulina platensis ingestion on the abnormal biochemical and oxidative stress parameters in the pancreas and liver of alloxan-induced diabetic rats - Ourida Aissaoui; Malek Amiali; Nora Bouzid; Khaled Belkacemi; Arezki Bitam (Taylor & Francis Group, 2017)
Context: Previous studies have shown that Spirulina platensis Gomont (Phormidiaceae) (SP) extract has beneficial effects on many disease conditions. The putative protective effects of SP were investigated in diabetic rats. Objective: The current study investigates the antioxidant effects of SP in diabetic Wistar rats. Materials and methods: Alloxan monohydrate (150 mg/kg body weight) was intraperitoneally administrated to induce diabetes. An aqueous suspension of SP powder in distillate water (10% w/v) was administrated orally by gavage (1 mL/day) for 50 days. Histopathological, biochemical and antioxidant analyses were performed. Glycemia, liver function and HOMA-IR were assessed using Spinreact and ELISA kits. Results: SP exhibited high-antioxidant activity. The IC50 values of the SP aqueous extract were 70.40 and 45.69 mg/L compared to those of the standard antioxidant BHT, which were 27.97 and 19.77 mg/L, for the DPPH and ABTS tests, respectively. The diabetic animals showed a significant increase in glycaemia (from 4.05 to 4.28 g/L) and thiobarbituric acid reactive substances (50.17 mmol/g protein) levels. Treatment with SP significantly reduced glycaemia by 79% and liver function markers [glutamate pyruvate transaminase (GPT), glutamate oxaloacetate transaminase (GOT) and alkaline phosphatase (Alk-p)]) by 25, 36 and 20%, respectively, compared to that of the controls. There was a significant increase in superoxide dismutase (48%), total antioxidant status (43%), glutathione peroxidase (37%) and glutathione reductase (16%) in the diabetic rats treated with SP. Discussion and conclusion: These results showed that SP has high antioxidant activity, free radical scavenging, antihyperglycemic and hepatoprotective effects in diabetes.